Soccer above all? Analysis of academic and vocational education among female soccer players in the German women's Bundesliga and 2nd women's Bundesliga - Ehnold, P.; Gohritz, A.; Lotzen, L.; Schlesinger, T. (Frontiers in Sports and Active Living, 2024)
Introduction Career-related (financial) reasons as well as advantages in terms of expanding social support systems, promoting a balanced lifestyle and personal development suggest that female soccer players should pursue academic or vocational education in parallel to elite sport. However, dual careers are fraught with challenges, mainly due to simultaneity in time and the associated conflicting goals. The aim of this article is to analyze the vocational or academic educational careers of professional female soccer players.